Sosialisasi Sosial Ekonomi Dan Budaya Ibadah Qurban Di Pondok Pesantren Miftahurrohmah Sukarata Purwakarta - Jalaludin, Jalaludin; Sopian, Ahmad Ali; Suryana, Eka Ahadiyat (STIE Syariah Indonesia Purwakarta, 2021)
Sacrificial worship is the worship of slaughtering sacrificial animals which is held every year by Muslims around the world, precisely when celebrating Eid al-Adha. Thus, the qurban worship will indirectly have an impact on the socio-economic and cultural conditions of the community where the qurban worship is carried out. From the socio-economic aspect, qurban worship is not only limited to religious rituals but can also be a driving force for the community's economy, especially in the procurement of sacrificial animals. Next in the socio-cultural aspect is how qurban worship can change people's lifestyles to be simpler which is far from consumerism and excessive lifestyles. The problem that has occurred in the community is the lack of public awareness (congregations) about the wisdom of qurban worship, especially from the socio-economic and cultural aspects. This community service is carried out to increase public awareness (congregations) of the wisdom of qurban worship, especially from the socio-economic and cultural aspects. This activity was carried out at the Miftahurrohmah Islamic Boarding School Sukarata Kab. Purwakarta. The approach taken is lectures and discussions, namely by providing explanations of the material in tutorials and discussions as well as providing examples of the management and implementation of qurban worship that can increase the socio-economic and cultural impact of the community.